The Effect of Service Quality on Customer Satisfaction at Banua Coffee Cafe in Makassar City - Musa, Ichwan; Pahlevi, Cepi; Sudirman, Indrianty; Sumardi (Economics and Business Journal (ECBIS), 2023)
The goal of this study is to ascertain how the level of service at Cafe Banua Coffee in Makassar City affects customer satisfaction. The research method utilized in this file is a quantitative research approach with an associative research type. This study found that service quality has an impact on customer satisfaction at Café Banua Coffee in Makassar city. Quantitative research is a research method based on the positivist philosophy, used to examine specific populations or samples. Data collection uses research instruments, and data analysis is quantitative in nature with the aim of testing predetermined hypotheses. This suggests that the business might raise client happiness by enhancing the caliber of services offered.